SARS-CoV-2 bivalent mRNA vaccine with broad protection against variants of concern - Ma, Qinhai; Li, Man; Ma, Lin; Zhang, Caroline; Zhang, Hong; Zhong, Huiling; Wen, Jian; Wang, Yongsheng; Yan, Zewei; Xiong, Wei; Wu, Linping; Guo, Jianmin; et al. (Frontiers in Immunology, 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant has rapidly spread around the globe. With a substantial number of mutations in its Spike protein, SARS-CoV-2 Omicron variant is prone to immune evasion and led to the reduced efficacy of approved vaccines. Here we developed a novel bivalent mRNA vaccine, RBMRNA-405, comprising a 1:1 mix of mRNAs encoding both Delta-derived and Omicron-derived Spike proteins. We evaluated the immunogenicity of RBMRNA-405 in BALB/c mice and compared the antibody response and prophylactic efficacy induced by monovalent Delta or Omicron-specific vaccine with the bivalent RBMRNA-405 vaccine in SARS-CoV-2 variants challenge. Results showed RBMRNA-405 vaccine could generate broader neutralizing antibody responses against both Wuhan-Hu-1 and other SARS-CoV-2 variants, including Delta, Omicron, Alpha, Beta, and Gamma. RBMRNA-405 efficiently blocked infectious viral replication and lung injury in both Omicron- and Delta-challenged K18-ACE2 mice. Taken together, our data suggest RBMRNA-405 is a promising bivalent SARS-CoV-2 vaccine with broad-spectrum efficacy for further clinical development.